Good practices for the translation, cultural adaptation, and linguistic validation of clinician-reported outcome, observer-reported outcome, and performance outcome measures - Shawn McKown; Catherine Acquadro; Caroline Anfray; Benjamin Arnold; Sonya Eremenco; Christelle Giroudet; Mona Martin; Dana Weiss (SpringerOpen, 2020)
Abstract Within current literature and practice, the category of patient-reported outcome (PRO) measures has been expanded into the broader category of clinical outcome assessments (COAs), which includes the subcategory of PRO, as well as clinician-reported outcome (ClinRO), observer-reported outcome (ObsRO), and performance outcome (PerfO) measure subcategories. However, despite this conceptual expansion, recommendations associated with translation, cultural adaptation, and linguistic validation of COAs remain focused on PRO measures, which has created a gap in specific process recommendations for the remaining types. This lack of recommendations has led to inconsistent approaches being implemented, leading to uncertainty in the scientific community regarding suitable methods. To address this gap, the ISOQOL Translation and Cultural Adaptation Special Interest Group (TCA-SIG) has developed recommendations specific to each of the three COA types currently lacking such documentation to support a standardized approach to their translation, cultural adaptation, and linguistic validation. The recommended process utilized to translate ObsRO, ClinRO and PerfO measures from one language to another aligns closely with the industry standard process for PRO measures. The substantial differences between respondent categories across COA types require targeted approaches to the cognitive interviewing procedures utilized within the linguistic validation process, including the use of patients for patient-facing text in ClinRO measures, and the need to interview the targeted observers for ObsROs measures.